Genetic determinants of Vitamin D deficiency in the Middle Eastern Qatari population: a genome-wide association study - Hendi, Nagham Nafiz; Al-Sarraj, Yasser; Ismail Umlai, Umm-Kulthum; Suhre, Karsten; Nemer, Georges; Albagha, Omar (Frontiers in Nutrition, 2023)
Epidemiological studies revealed that Middle Eastern countries have the highest prevalence of Vitamin D deficiency. However, research on the impact of genetic loci and polygenic models related to Vitamin D has primarily focused on European populations.We conducted the first genome-wide association study to identify genetic determinants of Vitamin D in Middle Easterners using a whole genome sequencing approach in 6,047 subjects from the Qatar Biobank (QBB) project. We identified a variant in a known locus for the group-specific component gene (GC), rs2298850 (P-value = 1.71 × 10 -08 , Beta = -0.1285). A GWAS meta-analysis combining the QBB cohort with previous UK Biobank data from recent European GWAS (N = 345,923 individuals) identified two novel variants at a known locus that reached the GWAS threshold, namely rs67609747 and rs1945603 on chromosome 11. We found a moderately high heritability of Vitamin D, estimated at 18%, compared to Europeans. We evaluated the performance of European-derived polygenic risk scores in the QBB cohort using UK Biobank data. Despite the lower predictive performance of Vitamin D levels in Qataris compared to Europeans, these scores were significantly linked to Vitamin D deficiency risk within the QBB cohort. This novel study reveals the genetic architecture contributing to Vitamin D deficiency in the Qatari population, emphasizing the genetic heterogeneity observed across different populations.